The regulatory influence of variations in plant traits among different rice varieties on greenhouse gas emissions in paddy fields - Fan, Mao; Yang, Xueting; Raheem, Abdulkareem; Zhang, Jian; Wang, Yan; Zhang, Jun; Hang, Xiaoning (Frontiers in Agronomy, 2026)
Methane (CH4) and nitrous oxide (N2O) are the two most important greenhouse gases following carbon dioxide (CO2). However, existing research on the relationship between rice plant morphological traits and GHG emissions remains relatively limited, often focusing only on individual or a few plant characteristics. To address this research gap, a field experiment was conducted in Chongqing from April to August 2024. Five locally promoted hybrid rice varieties, which are widely cultivated in the region, were selected as experimental materials. The CH4 and N2O emissions of these varieties throughout their entire growth cycle were continuously monitored using the static chamber-gas chromatography method. Concurrently, the morphological traits of both the above-ground components and root systems of the rice plants were quantified.The results revealed significant varietal differences in CH4 and N2O emissions. CH4 emissions followed a unimodal trend, peaking during the panicle emergence to full heading stage. In contrast, N2O emissions peaked after field drainage and drying. Cumulative CH4 emissions ranged from 314.6 to 443.4 kg·ha-1, with the variety ‘Qxiangyou 352’ exhibiting significantly lower emissions than the others. Cumulative N2O emissions ranged from -0.049 to 0.165 kg·ha-1, showing no significant differences among varieties. Correlation analysis indicated that CH4 flux was highly significantly positively correlated with plant height, leaf area index (LAI), aboveground dry biomass, and root dry biomass, but highly significantly negatively correlated with root oxidation activity (ROA). Similarly, N2O flux was highly significantly positively correlated with plant height, LAI, root volume, and root dry biomass, and significantly negatively correlated with ROA. Overall, ‘Qxiangyou 352’ not only achieved a relatively high yield of 11.2 t·ha-1, but also demonstrated the lowest global warming potential (GWP) of 8.8 t CO2e·ha-1 and the lowest greenhouse gas intensity (GHGI) of 0.8 t CO2e·t-1, highlighting its promising low-carbon and high-yield characteristics.